Analisis Pembelajaran Matematika Sekolah Dasar - Dwi Ersi Destari; Rina Indriani; Eka Ersi Destari (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Learning is the process of children getting to know knowledge that aims to increase knowledge as a basis for forming behavior. The learning process is carried out so that children experience behavioral changes and gain an overall improvement in knowledge, skills, and attitudes. Learning is very closely related to daily life, therefore it is important for children to learn continuously, one of which is through learning mathematics. Mathematics learning has a very important role in the sustainability of children's education because mathematics is one of the fundamental non-physical tools in the world of education and daily life. Through mathematics learning, children are trained to think logically, systematically, critically, and creatively in solving various problems. In addition, mathematics helps children solve calculation problems that are often encountered in daily activities, such as counting money, measuring length, time, and distance, and interpreting simple data. Mathematics learning also plays a role in developing the ability to reason and make appropriate decisions. Therefore, mathematics learning is a subject that must be followed because it has a great influence on thinking skills, learning independence, and children's readiness to face life challenges and scientific development in the future.